Recovery of 1-butyl-3-methylimidazolium-based ionic liquids - Idaham, N.F. (2014)
Ionic liquids have been recognized as an alternative solvent applicable in synthesis, separation, catalysis and electrochemistry. However, the synthesis costs, performance efficiencies and problems related to waste waters contaminated with ionic liquids are the major issues that need to be considered. Thus, recovery method is one of the alternatives to overcome the current issues. 1-butyl-3-methylimidazolium-based ionic liquids were chosen for the study. The recovery process was conducted in two steps; water-washing and recovery using solvent. All the selected ionic liquids were extracted with water and BMIM CH3SO4 was 100 recovered. However the ionic liquids contained high percentage of water which may change the properties of the ionic liquids. This current work has studied not only on the performance of recovery, but also on the properties and the behaviour of the ionic liquids to be further reused in a particular application. Â© (2014) Trans Tech Publications, Switzerland.